Liturgy, Ritual, and Secularization in Nineteenth-Century British Literature, By Joseph McQueen - Vernon, Amanda B. (Literature and theology, 2025)
In Liturgy, Ritual, and Secularization in Nineteenth-Century British Literature, Joseph McQueen calls us to rethink the modern conception of religion as "e